2009
DOI: 10.1371/journal.pone.0005751
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Feelings: Characterization of Trait Alexithymia on Emotion Regulation Strategies and Cognitive-Emotional Processing

Abstract: BackgroundAlexithymia, or “no words for feelings”, is a personality trait which is associated with difficulties in emotion recognition and regulation. It is unknown whether this deficit is due primarily to regulation, perception, or mentalizing of emotions. In order to shed light on the core deficit, we tested our subjects on a wide range of emotional tasks. We expected the high alexithymics to underperform on all tasks.MethodTwo groups of healthy individuals, high and low scoring on the cognitive component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
190
0
26

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(239 citation statements)
references
References 45 publications
23
190
0
26
Order By: Relevance
“…Among these studies, alexithymia was found to modulate electrophysiological responses to emotional information from speech prosody, suggesting an automatic affective processing deficit in HA (Goerlich et al, 2012(Goerlich et al, , 2011) associated with reduced activation in the right superior temporal gyrus and amygdala during affective prosody categorization . Furthermore, HA tended to respond slower than LA when they had to categorize an emotion conveyed by the tone of a spoken sentence (with an incongruent emotional content) (Swart et al, 2009), and HA made more errors in identifying disgust expressed through nonsense syllables spoken in an emotional intonation (Goerlich et al, 2012). However, to date, only one study (Heaton et al, 2012) has investigated these alexithymic features using nonverbal emotional vocalizations (NEV) (e.g., laughter, sighs, wails, cries, and groans) (see e.g., Sauter and Eimer, 2010;Sauter and Scott, 2007;Scott et al, 1997) and found a reduced ability to categorize NEV (i.e., happy, sad, anger, surprise, fear and disgust) associated to the level of alexithymia.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Among these studies, alexithymia was found to modulate electrophysiological responses to emotional information from speech prosody, suggesting an automatic affective processing deficit in HA (Goerlich et al, 2012(Goerlich et al, , 2011) associated with reduced activation in the right superior temporal gyrus and amygdala during affective prosody categorization . Furthermore, HA tended to respond slower than LA when they had to categorize an emotion conveyed by the tone of a spoken sentence (with an incongruent emotional content) (Swart et al, 2009), and HA made more errors in identifying disgust expressed through nonsense syllables spoken in an emotional intonation (Goerlich et al, 2012). However, to date, only one study (Heaton et al, 2012) has investigated these alexithymic features using nonverbal emotional vocalizations (NEV) (e.g., laughter, sighs, wails, cries, and groans) (see e.g., Sauter and Eimer, 2010;Sauter and Scott, 2007;Scott et al, 1997) and found a reduced ability to categorize NEV (i.e., happy, sad, anger, surprise, fear and disgust) associated to the level of alexithymia.…”
Section: Introductionmentioning
confidence: 95%
“…Most previous studies have involved visual stimuli like emotional facial expressions (EFE), pictures, videos or words (Berthoz et al, 2002;Franz et al, 2004;Meriau et al, 2006Meriau et al, , 2009Nielson and Meltzer, 2009;Pollatos and Gramann, 2011;Ridout et al, 2010;Vermeulen and Luminet, 2009;Vermeulen et al, 2006Vermeulen et al, , 2008 angry faces, and tend to rate fearful faces as less intense than individuals with a lower level of alexithymia (LA) (Prkachin et al, 2009). Despite the importance of emotions conveyed through the auditory channel in social interactions, few studies have examined their processing in alexithymia (Goerlich et al, 2012(Goerlich et al, , 2011Schafer et al, 2007;Swart et al, 2009;Vermeulen et al, 2010). Some of these studies linked deficits in the identification of affective prosody to a high level of alexithymia.…”
Section: Introductionmentioning
confidence: 99%
“…Alexithymia is a trait in which individuals have a reduced ability to regulate, identify, and communicate feelings or emotions (Franz, Schaefer, Schneider, Sitte, & Bachor, 2004;Sifneos, 1973). Importantly, alexithymia seems to be characterized by an emotion regulation style overreliant on suppression, rather than reappraisal, strategies (e.g., Dimsdale et al, 1986;Franz et al, 2004;Grabe et al, 2004;Kessler, Kammerer, Hoffmann, & Traue, 2010;Richter et al, 2006;Swart, Kortekaas, & Aleman, 2009). For instance, Kessler et al found a positive relationship between TAS scores and individual differences in expressive suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the interest in studying the relationship between alexithymia and emotion recognition, there are only a few studies addressing the role of alexithymia in facial recognition tasks with parts of the face, such as the work of Swart, Kortekaas, andAleman (2009) andSchimmenti (2016). This restricted condition is expected to make these recognition tasks considerably more difficult.…”
mentioning
confidence: 99%